ALIGNING STRATEGIC OBJECTIVES TO CORPORATE GOVERNANCE OBJECTIVES IN CONSTRUCTION PROFESSIONAL SERVICE FIRMS - Frank Boateng; De-Graft Owusu-Manu; Michael Adesi; Erika Parn; David John Edwards (Journal of Construction Project Management and Innovation, 2019)
Securing business profitability can inadvertently create conflict between the pursuit of strategic corporate objectives and corporate governance objectives while simultaneously reducing stakeholder protection. This imbalance has culminated in several high-profile corporate scandals orchestrated by top management – consequently, this research seeks to establish a nexus between strategic corporate objectives and corporate governance objectives within construction professional service firms. –The study is positioned within the positivist philosophical tradition and adopts a quantitative approach that used a survey questionnaire to collect data form construction professional service firms.115 survey questionnaires were administered to respondents using the purposive sampling technique in which 80 completed questionnaires were retrieved for an analysis representing a response rate of 69.5 per cent. The analysis results revealed a significant relationship at p < 0.05 between strategic corporate objectives and corporate governance objectives focusing on credibility, conflict resolution, channels of reporting, influencing performance, transparency in initial public offerings (IPOs); control of corporate corruption; and reputation of the firm. Aligning strategic corporate objectives to corporate governance objectives is rare in literature. This paper establishes a critical discussion which could culminate into strategies for aligning corporate strategic objectives and corporate governance objectives in the future. Corporate planners, corporate governance experts and managers of corporate organisations will benefit from the strategic direction provided by this study. Such will help circumvent management board-room politics and avoid potential corporate scandals and confusions by ensuring alignment between strategic objectives and corporate governance objectives at all management levels within a firm.